A rat model of chronic moderate alcohol consumption and risk of decompression sickness - Buzzacott, Peter; Mazur, A.; Wang, Q.; Lambrechts, K.; Theron, M.; Guerrero, F. (2015)
© 2015, South Pacific Underwater Medicine Society. All rights reserved. Introduction: This study aimed to establish if chronic, moderate, pre-dive alcohol consumption had any affect upon susceptibility to decompression sickness (DCS) in rats. Methods: A treatment group of 15 rats were given water containing 12 mL·L-1 of ethanol for four weeks. Controls (n = 15) were given water. Both groups were compressed with air to 1,000 kPa, followed by staged decompression. An additional 30 control rats from a similar previous experiment were added, raising the control-treatment ratio to 3:1. Results: Rats in the treatment group consumed the equivalent of an 80 kg man drinking 2 L of 5% alcohol by volume beer per day, which is three times the recommended daily limit for men. Overall, comparing the treatment group with the combined control groups neither weight (P = 0.23) nor alcohol consumption (P = 0.69) were associated with DCS. Discussion: We observed that chronic, moderate alcohol consumption prior to compression was neither prophylactic nor deleterious for DCS in young, male rats.